2021
DOI: 10.1111/1365-2656.13532
|View full text |Cite
|
Sign up to set email alerts
|

Roadkill islands: Carnivore extinction shifts seasonal use of roadside carrion by generalist avian scavenger

Abstract: 1. Global road networks facilitate habitat modification and are integral to human expansion. Many animals, particularly scavengers, use roads as they provide a reliable source of food, such as carrion left after vehicle collisions. Tasmania is often cited as the 'roadkill capital of Australia', with the isolated offshore islands in the Bass Strait experiencing similar, if not higher, levels of roadkill. However, native mammalian predators on the islands are extirpated, meaning the remaining scavengers are like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…4e), probably because nocturnal devils consumed the resources before diurnal ravens discovered them. This finding supports previous findings that under low levels of competition raven populations on the Bass Strait islands prioritise scavenging on roadkill across the entire year even when other resources (e.g., invertebrates, fruit, seeds) are available [40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4e), probably because nocturnal devils consumed the resources before diurnal ravens discovered them. This finding supports previous findings that under low levels of competition raven populations on the Bass Strait islands prioritise scavenging on roadkill across the entire year even when other resources (e.g., invertebrates, fruit, seeds) are available [40].…”
Section: Discussionsupporting
confidence: 91%
“…In the Bass Strait region, anecdotal evidence suggests that forest-raven and feral-cat populations are growing on King Island [28, 49]. Enhanced opportunities to feed to on roadkill [40] and other carrion, as demonstrated in this study, may provide explanations for this apparent increase in abundance. Further research is needed to confirm whether these species are truly increasing in abundance.…”
Section: Discussionmentioning
confidence: 55%
“…This finding supports previous evidence that under low levels of competition raven populations on the Bass Strait islands prioritize scavenging on carrion, such as roadkill, across the entire year even when other resources (e.g. invertebrates, fruit, seeds) are available [50]. Both raven carcass use and carcass discovery by all species was reduced in wet forests, likely due to habitat preferences or reduced visibility in these environments.…”
Section: Discussionsupporting
confidence: 88%
“…In the Bass Strait region, anecdotal evidence suggests that forest raven and feral cat populations are growing on King Island [27]. Enhanced opportunities to feed to on roadkill [50] and other carrion, as demonstrated in this study, may provide explanations for this apparent increase in abundance. Further research is needed to confirm whether these species are truly increasing in abundance.…”
Section: Discussionmentioning
confidence: 59%
“…The relative absence of dingoes at carcass sites, along with similarly low rates of scavenging by red foxes and feral cats, is likely to have especially influenced the use of carcasses by brushtail possums who regularly feature in the diets of these three predators (Jones and Coman 1981;Newsome et al 1983;Dickman 1996;Vernes et al 2001;Kinnear et al 2002;Brook and Kutt 2011;Pascoe et al 2012;McComb et al 2018;Fleming et al 2021;Moseby et al 2021). Further still, recent findings in Australia have demonstrated that ravens, in the absence of top scavengers, scavenged across all four seasons and not only during the cooler months when other resources were low (Fielding et al 2021). Therefore, whether the relative absence of larger scavengers at carcass sites in this study aided mesoscavenger access to the food source is unknown; however, it could be reasonably expected if this resulted in reduced predation risk for the mesoscavengers and/or less competition for the food source.…”
Section: Discussionmentioning
confidence: 99%